Towards a dams safety management system for Angola - Camilo, V. (2015)
Dams have contributed to the human development and have brought many benefits, such as delivering hydropower, irrigating agricultural fields, supplying drinking water, or just for navigational and recreational purposes. Nevertheless, dams are critical structures that raise multiple concerns and risks associated with the ecological, social and economic impact. Angola has a rich and complex network of water basins and dams that serves different strategic purposes as defined in its water resource management policy and respective strategic plan that, namely, considers relevant to build new dams and to better operate the existent ones. In fact, some of the most important dams in Angola are equipped with safety management information devices that perform data collection and storage for infrastructural analysis and reporting. However, many of these systems are currently in a critical condition. The civil war of 1975-2002 took a toll on dam safety measures and systems and most of them are outdated or malfunctioning. The dams that are presently under construction, like Matala, will already be equipped with safety management devices that are able to perform measurement of variables such as displacement and discharges, among others. Yet, new and adequate legislation must be created for all these efforts to effectively take place: the National Dam Safety Plan may provide the answer and framework to this state of affairs. Additionally, in this paper we assert that a more complex and integrated system can help to achieve this plan. Hence, the main contribution of this paper is the proposal of the gestBarragens-2, a next-generation Dam Safety Management System (DSMS), particularly fitting for the geographic and political context of Angola. This DSMS highlevel architecture reflects our experience with the design, development and operation of a former DSMS in Portugal over this last decade, but also the state of art analysis and our own learning process, introspection and criticism. The gestBarragens-2 architectural view defines the complex integration of several subsystems in two complementary dimensions: the applicational and the technological. The applicational subsystems are mainly functional, while the technological subsystems provide crosscutting features that are widely used in the DSMS as a whole.